Uniplanar Nystagmus Associated with Perceptual and Cognitive Visual Dysfunction due to Presumed Focal Ischemic Occipital Cortical Atrophy: A Missed Diagnosis and New Observation - Swetha Sara Philip; Gordon N. Dutton; Liam Dorris (Case Reports in Pediatrics)
Uniplanar nystagmus has been described in relation to pathology of the brain stem, retina, optic nerve, sensory visual deprivation, periventricular leucomalacia, and drug toxicity. This paper describes a case of uniplanar nystagmus associated with features of higher visual dysfunction and a presumed focal insult to the occipital lobes following an episode of neonatal apnea.